Factors associated with early antenatal care attendance among women in Papua New Guinea: a population‐based cross‐sectional study - Abdul-Aziz Seidu (BMC, 2021)
Abstract Background Early initiation of antenatal care (ANC) is a key component of antenatal care, as suggested by the World Health Organisation (WHO). It helps in early identification and mitigation of adverse pregnancy-related complications. Despite this, a greater proportion of women worldwide still do not adhere to this recommendation. This study, therefore, sought to assess the prevalence and factors associated with early initiation of ANC among women in Papua New Guinea (PNG). Methods A population-based cross-sectional study was conducted among 4,274 women using data from the 2016-2018 PNG Demographic and Health Survey (PDHS). The outcome variable was early initiation of ANC. Bivariate (chi-square) and multivariable logistic regression analyses were done and statistical significance was set at p < 0.05. Results The prevalence of early ANC initiation was 23.0 % (CI = 20.8-24.6). The binary logistic regression analysis showed that working women had higher odds of early ANC attendance compared with those who were not working [AOR = 1.37, 95 %CI = 1.17 = 1.60]. The results also showed that women from Islands region had lower odds [AOR = 0.50, 95 %CI = 0.40-0.62] of early ANC attendance compared with those from Southern region. Finally, women with parity 3 had lower odds of early ANC attendance compared to those with parity 1[AOR = 0.64,95 % CI = 0.49-0.84]. Conclusions This study found a relatively low prevalence of early ANC uptake among women in PNG. The factors associated with early ANC attendance were region of residence, parity, and working status of mothers. To increase early ANC uptake, these factors should be considered when designing new policies or reviewing policies and strategies on ANC uptake to help increase ANC attendance, which can help in the reduction of maternal mortality.